The A-B-C of Content Learning in CLIL Settings: A call for contributions from Content-Pedagogy Specialists - Cristina Escobar Urmeneta (Universitat Autònoma de Barcelona, 2018)
The A-B-C of Content Learning in CLIL Settings section of CJ aims to become a forum where the role of PCK in CLIL can be explored collaboratively, thus helping to fill a gap in the field. With this purpose, The A-B-C invites content-area specialists and PCK-Language teacher tandems to make informed contributions about how best to approach the teaching and learning of their particular subject matter in language development settings such as CLIL and Immersion classrooms, or Language Reception programmes for newly arrived students with migration backgrounds.